Identification and modelling process of defining temperature gradient in airport pavement - Ahyudanari, E. (Taylor and Francis, 2014)
Preserving airport pavement means guarantying the safety operation of aircraft movements. There are four aspects that cause progressive pavement deterioration, i.e. the construction design and process, selected material, and maintenance management. One of the traffic aspects, jet engine exhaust, has not been discovered yet. The load pattern of the jet exhaust follows the schedule of aircraft traffic. The assumption held in this research is that the thermal load during aircraft movement may generate a high temperature, which is induced into pavement layers. The objective of this research is to determine the temperature gradient in the pavement, caused by the jet exhaust. This paper discusses the process of determining the temperature gradient in four stages, i.e. by carrying out the gap analysis, evaluation of pavement structures, determination of the load path and the magnitude, and defining the temperature gradient. The temperature gradient in the pavement layer is determined through the development of a model of cyclic loading. The thermal cyclic load follows the aircraft schedule pattern. The pavement temperature receives the thermal cyclic load of the sinusoid of solar radiation. The results indicate that the temperature of the pavement is increased and pavement temperature rises by 35 °C. However, after 60 seconds the remaining temperature of the pavement layer decreases to the initial temperature, which is caused by solar radiation. © 2014 Copyright © 2014 Vilnius Gediminas Technical University (VGTU) Press.